Verbal Communication Patterns of Traders in Buying and Selling Transactions - Wahyuni, Rani Sri; Komara, Mutiara Andayani (Universitas Suryakancana, 2024)
This study aims to find out the forms of verbal communication patterns used by traders who sell in the Rebo of Purwakarta Regency for indigenous buyers and the obstacles encountered in the process of buying and selling. This study uses a descriptive qualitative research method and a pragmatic approach. The data collection techniques used in this study include recording techniques, interviews, recording techniques, and documentary studies. While the research data concerns traders and buyers in buying and selling courses, the respondents are traders and men and women, young people, adults, or elderly who are in the rebo market area. Based on the results of research in the field, researchers obtained data according to which modes of communication of traders with buyers of Rebo took place mainly in a primary way, that is to say, face to face and using more than one language when buying and selling. reciprocal communication transactions between traders and buyers. Two-way communication follows in the negotiation process an explanation of the goods. At the same time, verbal communication occurs with questions and response between traders and buyers during the transaction. The language used in the purchasing process and in general is that of Sundanese, mixed and Indonesian traders, as they adapt to buyers.Keywords: patterns; traders; transactions of purchase; verbal communication